Acculturation influences on AAPI adolescent-mother interactions and adolescents' sexual initiation. - Kao, Tsui-Sui Annie; Loveland-Cherry, Carol; Guthrie, Barbara; Caldwell, Cleopatra H (Western journal of nursing research, 2011)
The purpose of this secondary analysis of data is to examine relationships among Asian American Pacific Islanders (AAPI) adolescents' level of acculturation, maternal influences, and age of sexual initiation. Selected predictive variables are based on the theoretical frameworks and literature review. The results indicate that for these adolescents speaking English at home was positively associated with maternal sexual discussion, mothers' perceptions of connectedness with their adolescents, adolescents' perceived maternal sexual expectations, and later sexual initiation at Wave 1. Adolescents' years of U.S. residency are positively associated with adolescents' level of perceived connectedness with their mothers and later sexual initiation at Wave 2. Adolescents' level of acculturation influence how they interacted with their mothers, perceived their mothers' sexual expectations, and when they decided to initiate sexual intercourse. Interventions to delay AAPI adolescents' sexual debut should consider factors related to AAPI adolescents' and their mothers' levels of acculturation.
Keywords: Acculturation; Adolescent; Adolescent Behavior; Female; Humans; Longitudinal Studies; Mother-Child Relations; Oceanic Ancestry Group; Sexual Behavior; United States